A Flexible Photoactive Titanium Metal–Organic Framework Based on a [TiIV3(μ3‐O)(O)2(COO)6] Cluster. Issue 47 (25th September 2015) - Bueken, Bart; Vermoortele, Frederik; Vanpoucke, Danny E. P.; Reinsch, Helge; Tsou, Chih‐Chin; Valvekens, Pieterjan; De Baerdemaeker, Trees; Ameloot, Rob; Kirschhock, Christine E. A.; Van Speybroeck, Veronique; Mayer, James M.; De Vos, Dirk
Abstract: The synthesis of titanium–carboxylate metal–organic frameworks (MOFs) is hampered by the high reactivity of the commonly employed alkoxide precursors. Herein, we present an innovative approach to titanium‐based MOFs by the use of titanocene dichloride to synthesize COK‐69, the first breathing Ti MOF, which is built up from trans ‐1, 4‐cyclohexanedicarboxylate linkers and an unprecedented [Ti IV 3 (μ3 ‐O)(O)2 (COO)6 ] cluster. The photoactive properties of COK‐69 were investigated in depth by proton‐coupled electron‐transfer experiments, which revealed that up to one Ti IV center per cluster can be photoreduced to Ti III while preserving the structural integrity of the framework. The electronic structure of COK‐69 was determined by molecular modeling, and a band gap of 3.77 eV was found. Abstract : A breath of fresh air : Titanocene dichloride was used as the metal source in an innovative synthetic approach to titanium‐based metal–organic frameworks (MOFs). In this way, a breathing Ti MOF (designated COK‐69) featuring a photoactive trinuclear cluster was built up from trans ‐1, 4‐cyclohexanedicarboxylate and an unprecedented, photoactive [Ti IV 3 (μ3 ‐O)(COO)6 ] inorganic building unit (see picture).